Numerical and Experimental Investigation of the Influence of Backpressure on a Confined Impinging Jet for Small Nozzle-to-plate Spacing - K. Zhu; R. Shen; T. Sun; G. Chen; J. Ding (Journal of Applied Fluid Mechanics, 2024)
In order to further extend understanding of the heat transfer characteristics under an enclosed area, the influence of backpressure on a single impingement jet with small nozzle-to-plate spacing (H/D) is studied. Particle image velocimetry (PIV) technique and a commercial fluid dynamics solver (CFD) are respectively employed to investigate the fluid dynamics of the impinging jet, with a Reynolds number (Re) of 3462–6125, at a small nozzle-to-plate spacing (H/D) of 0.25–1.25. Experimental data are in well agreement with numerical simulation data. The findings indicate that the H/D ratio significantly influences the formation of backpressure in the flow field. The backpressure then influences the boundary layer velocity on the impingement surface, in turn affecting the impingement surface's heat transfer characteristics. In addition, a turning point in the horizontal velocity curve of H/D = 0.4 is found for an entire range of jet heights, which is independent of the Reynolds number (Re).